Translucency and color differences of polycrystalline ceramic materials before and after layering - João Carlos Roque; Joana Lima Hermínio; Diogo Viegas; João Martins; Luís Santos; Jaime Portugal (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
Objective: To evaluate the transmittance (%T) and color difference (∆E*) of six zirconia core materials compared to alumina, over eight colored substrates before and after ceramic application. Methods: Experimental groups (n=5) of standardized disk-shaped cores of alumina, white zirconia, medium-colored zirconia, Ice Translucent, and Prettau (white and D3 colored) were veneered to a uniform thickness to convenient color by layering. Their %T and ∆E* over eight different substrates were determined before and after glazing. Data were analyzed with Kruskal-Wallis and Mann-Whitney tests (α<0.05). Results: %T and ∆E* values were significantly different (p<0.001) before and after ceramic application for all materials. Regarding %T, Prettau white zirconia was the most affected, overpassing alumina. Colored zirconia cores decreased %T equally. In terms of ∆E*, zirconia materials initially performed high above the clinically acceptable threshold but were under it after ceramics application. White zirconia was the only material to perform below the clinical perceptibility threshold. Alumina initially performed under the clinically acceptable threshold for two substrates, but after ceramic application, only performed under the clinical perceptibility threshold over four. Substrates influenced ∆E* values of all core materials but were only evident on three of them. Conclusions: Core materials influenced %T and ∆E* values. Colored zirconia cores showed less %T than white cores and both less than alumina before and after ceramic application. After ceramic application, all materials performed under the clinically acceptable threshold over all the substrates. Substrates have more influence on ∆E* values before ceramic application.